4 Maccabees - DeSilva, David Arthur (Guides to Apocrypha and Pseudepigrapha., 1998)
Hellenistic Greek society offered many advantages to the Jew who was willing to relax Torah for the sake of easier relations with the dominant culture. 4 Maccabees was written to reassure Jewish readers that Torah was in fact the sole path to the perfection of the virtues honoured in Greek culture, as it freed the diligent devotee from slavery to the desire, emotion and the domination of pain and pleasure. In brief compass, deSilva provides a detailed look at the rhetorical and philosophical strategy of the author of 4 Maccabees, who redirects the hearers' desire for honour and advancement tow.